Lipid peroxidation and antioxidative enzyme activities in childhood epilepsy - TÜRKDOĞAN, DİLŞAD (B C DECKER INC, 2002)
This study aimed to investigate the relationship among lipid peroxidation, subsequent activation of scavenger enzymes (superoxide dismutase and glutathione peroxidase), and the presence of structural abnormality in 52 epileptic children receiving monotherapy (medically responsive) or polytherapy (medically intractable). Plasma lipid peroxidation in epileptic patients with abnormal magnetic resonance imaging (MRI) findings significantly increased as compared with that of 16 healthy children (P<.05), whereas antioxidant enzymes were not significantly affected. Both medically controlled and intractable children with normal MRI had higher activities of superoxide dismutase than those of controls (P<.05). The activity of superoxide dismutase in epileptic patients with structural abnormality did not significantly change as compared with controls. Activity of glutathione peroxidase in all of the epileptic children was not significantly different from controls. The activity of antioxidant enzymes or plasma malonyldialdehyde levels did not correlate with duration of epilepsy, frequency of seizures (> one seizure per month or not), and the presence or localization (focal, multifocal, or generalized) of electroencephalographic or MRI abnormalities. Increased plasma lipid peroxidation may be causally related to the presence of structural abnormality rather than ongoing epileptic activity or therapy status.
Keywords: GLUTATHIONE-PEROXIDASE; SUPEROXIDE-DISMUTASE; RAT-BRAIN; CHILDREN